Influence of the block geometry on the voltammetric response of partially blocked electrodes: Application to interfacial liquid-liquid kinetics of aqueous vitamin B-12S with random arrays of femtolitre microdroplets of dibromocyclohexane - Chevallier, F; Davies, T; Klymenko, O; Jiang, L; Jones, T; Compton, R (2005)
The cyclic voltammetric response of electrodes modified with catalytically reactive blocks is simulated using finite difference methods. The responses of three different models using various block geometries are studied. The results are used to determine kinetic parameters of coupled liquid|liquid interfacial reactions. First, we examine the liquid-liquid reaction between aqueous vitamin B12S and pure trans-dibromocyclohexane (DBCH) microdroplets immobilized on a basal plane pyrolytic graphite (bppg) surface, immersed in an aqueous solution of vitamin B12. Second, cyclic voltammetry on electrodes modified with microdroplets of DBCH diluted in dodecane is employed to determine the apparent bimolecular interfacial rate constant for the initial step in the DBCH(oil)/B12S(aq) reaction. The results are compared with a previous SECM/ITIES study of a similar reaction. © 2005 Elsevier B.V. All rights reserved.